Monuments for Posterity : Self-Commemoration and the Stalinist Culture of Time - Kalashnikov, Antony, 1991- (Book collections on Project MUSE., 2023)
"This book examines Stalinist sculptural and architectural monuments, which were tasked with 'immortalizing the memory' of the era, for the edification of future generations. The book analyzes how this objective affected monument design and what factors prompted the popular yearning to be remembered-both in the Soviet Union and beyond its borders."--